Metode Saintifik Dalam Meningkatkan Hasil Belajar Tematik Siswa Madrasah Ibtidaiyah - Muhammad Alfin Rifai; Daluti Delimanugari; Ana Dwi Wahyuni (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2019)
This study aims to determine the use of a scientific approach to learning outcomes in theme 5 case studies of sixth grade students of MI YAPPI Karangwetan. The implementation of learning is oriented towards the end result only, so that learning in the classroom becomes less active. This research method is Classroom Action Research, the sample of this research uses a simple sampling technique, namely class. Data collection techniques consist of tests, questionnaires, observations, and documentation. The research instrument consisted of learning questions in the cognitive domain. Based on the research results obtained, the scientific approach provides better learning outcomes. It is proven by the increase in learning outcomes for class VI who were treated with a scientific approach compared to the previous learning methods, namely the lecture, discussion and question and answer methods. This is evidenced by the achievement of student learning outcomes which initially only reached 50% of students who scored above the KKM by using the scientific method, the value of student learning outcomes increased to 100% above the KKM.